KESULITAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Fitri, Maria (Inspiratif Pendidikan, 2019)
Learning difficulties is a condition where students cannot learn naturally, due to threats, obstacles or disturbances in learning. Broadly speaking, the factors that cause learning difficulties consist of two kinds, namely the internal factors of students, namely things / circumstances that arise from within themselves students and external factors of students, namely things / circumstances circumstances that come from outside the learner. Besides being required to be skilled in delivering subject matter, teachers are also required to be able to recognize their students. Lessons will easily reach the educational goals if an educator knows his students very well. Recognizing students has an urgency that is able to get closer to the relationship between educators and students, not only recognizing the names of students, or their personality and character, but educators are also required to be able to recognize students’ learning difficulties in order to be able to diagnose these difficulties so that they become a consideration in develop learning plans.